2016
DOI: 10.1007/s11739-016-1470-2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of point of care ultrasound to identify the source of infection in septic patients: a prospective study

Abstract: Sepsis is a rapidly evolving disease with a high mortality rate. The early identification of sepsis and the implementation of early evidence-based therapies have been recognized to improve outcome and decrease sepsis-related mortality. The aim of this study was to compare the accuracy of the standard diagnostic work-up of septic patients with an integrated approach using early point of care ultrasound (POCUS) to identify the source of infection and to speed up the time to diagnosis. We enrolled a consecutive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 24 publications
0
35
0
3
Order By: Relevance
“…Previous studies have demonstrated the utility of point of care ultrasound (POCUS) in the evaluation of patients with sepsis. 11,12 However, limited data exists on the evaluation of POCUS for septic cardiomyopathy. There are no specific or sensitive sonographic signs for identifying sepsis or septic cardiomyopathy (SCM) other than those associated with infection at a specific site.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the utility of point of care ultrasound (POCUS) in the evaluation of patients with sepsis. 11,12 However, limited data exists on the evaluation of POCUS for septic cardiomyopathy. There are no specific or sensitive sonographic signs for identifying sepsis or septic cardiomyopathy (SCM) other than those associated with infection at a specific site.…”
Section: Introductionmentioning
confidence: 99%
“…Step five is “etiology explored.” Diagnose the etiology by integrating the above four steps; search for the source of infection according the clues extracted from the focused ultrasound exam; additional ultrasound exams or other tests should applied if needed. The clues are listed as examples: acute cor pulmonale indicates pulmonary embolism, unreasonable ventilation setting, or severe mismatch of the ventilation and flow representing ARDS [ 45 ]; acute increase in PAOP derives from decrease in systolic function, left side valve insufficiency, hypervolemia, or decreased myocardium compliance [ 66 ]; diffuse sonointerstitial syndrome (SIS) indicates hypervolemic pulmonary edema, cardiogenic pulmonary edema, leakage pulmonary edema, acute pneumonitis, pulmonary alveolar proteinosis, and chronic pulmonary fibrosis [ 6 , 37 , 67 ]; consolidation with shred sign in lung ultrasound indicates pneumonia [ 68 70 ]; hypoechoic yet heterogeneous at plural cavity indicates hemothorax or pyothorax [ 32 , 33 ]; echogenic dots in free fluid indicate abscessus [ 33 , 71 ]; echogenic dots in physiology cavity indicate infection [ 33 , 71 ] and so forth. With the clues above, we can clearly know what to do next and the diagnosis procedure can be efficient.…”
Section: The Piepear Workflow: a Critical Care Ultrasound Based 7-mentioning
confidence: 99%
“…There have been many consensus statements describing and supporting the accurate use of POCUS by EM physicians . From US‐guided procedures to diagnostic algorithms, POCUS has proven to benefit patients at the bedside within the acute setting . Despite this, there still remain areas of contention.…”
Section: Introductionmentioning
confidence: 99%